Ocular Melanoma Clinical Characteristics in Sardjito Hospital Yogyakarta: A 5-Year Retrospective Study: Oral Presentation - Observational Study - General practitioner - Kevin Setiawan (Majalah Oftalmologi Indonesia, 2023)
Abstract Introduction & Objectives : Ocular melanoma is a rare and potentially deadly type of cancer that affects the cells in the eye responsible for producing pigmentation. Unlike skin melanoma, which is more common and arises from the skin, ocular melanoma occurs within the eye itself, often developing in the choroid, ciliary body, or iris. Although rare, ocular melanoma is the most common primary cancer of the eye in adults. This abstract aims to provide the prevalence and clinical characteristics of ocular melanoma in a tertiary referral hospital in Yogyakarta. Methods : A retrospective study was conducted in 2022. Medical records of patients diagnosed with ocular melanoma between January 2016 – December 2020 were analyzed. Prevalence rates, patient demographic, clinical characteristics, type of ocular melanoma, and treatment were evaluated. Results : Ten patients were included in the study and the ratio was equal in men and women. Patients came from East Java (40%), Central Java (30%), and Yogyakarta Province (30%). The initial symptom was a predominantly growing spot on the eye (60%). All patients had unilateral ocular melanoma, predominantly in the left eye (80%). The origin of the tumor was conjunctival melanoma (30%), orbital melanoma (30%), uveal melanoma (20%), choroidal melanoma (10%), and eyelid melanoma (10%). The modality of treatment is predominantly surgical with chemotherapy (30%). Conclusion : The most common initial symptom of ocular melanoma was a growing spot on the eye and most cases were treated by surgery with chemotherapy.